2022
DOI: 10.1186/s13023-022-02233-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of living donor liver transplantation from heterozygous carrier donors in children with propionic acidemia

Abstract: Background Current world experience regarding living donor liver transplantation (LDLT) in the treatment of propionic acidemia (PA) is limited, especially in terms of using obligate heterozygous carriers as donors. This study aimed to evaluate the clinical outcomes of LDLT in children with PA. Methods From November 2017 to January 2020, 7 of the 192 children who underwent LDLT at our institution had been diagnosed with PA (median age, 2.1 years; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A growing number of patients with monogenic metabolic liver diseases (such as urea cycle disorders, maple syrup urine disease, MMA, and PA) undergo LT worldwide [17][18][19][20][21]. The explanted livers from those liver transplant recipients with noncirrhotic liver-based metabolic disorders are morphologically, structurally, and functionally normal except for definite metabolic deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of patients with monogenic metabolic liver diseases (such as urea cycle disorders, maple syrup urine disease, MMA, and PA) undergo LT worldwide [17][18][19][20][21]. The explanted livers from those liver transplant recipients with noncirrhotic liver-based metabolic disorders are morphologically, structurally, and functionally normal except for definite metabolic deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The information garnered from this article can serve as an important source of clinical evidence and procedures involving LT for the treatment of HoFH. Our center is particularly suited for conducting this review as nearly 1500 LTs, including over 800 pediatric LTs and almost 700 living donor LTs, have been performed at our center [4,5]. Our study protocol conforms to the ethical guidelines of the 1975 Declaration of Helsinki and was approved by the local ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…This study also demonstrated that hepatic expressions of PCCA and PCCB was consistent at the protein level in both heterozygous donor and the healthy donor for the first time. Liver supply from relatives carrying heterozygous genes is relatively easy to obtain and less burdensome for patients’ families [ 85 ] (Additional file 1 ). For children with mild PA, prophylaxis is recommended for patients under one year of age [ 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is undeniable that patients with PA may still develop complications even after LT, such as renal failure, hepatic artery thrombosis [ 86 , 87 ]. However, LT can largely prevent metabolic decompensation, achieve protein diet liberalization, improve neurodevelopmental delay to some extent, and may even treat cardiomyopathy [ 85 ].…”
Section: Introductionmentioning
confidence: 99%